Pengaruh Kebutuhan Aktualisasi Diri Dan Penghargaan Terhadap Prestasi Kerja Polri - Mia Ramdani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The background of this research is the not yet optimal work performance of employees which can be seen from the fact that there are still several criteria that have not reached the targets that have been set, although there are some that have achieved the target for example in 2020 on high dedication in carrying out tasks and disclosing cases of prostitution. This is thought to be caused by the not optimal need for self-actualization and appreciation which can be seen from the lack of initiative from employees and the decline. The purpose of this study was to find out 1) The effect of self-actualization needs on employee performance in the Purwaharja Sector Police in Banjar City; 2) The effect of appreciation on employee performance in the Banjar City Purwaharja Sector Police; 3) The effect of self-actualization needs and appreciation on employee performance in the Purwaharja Sector Police in Banjar City. In this study used a survey method with a quantitative data approach. The population in this study were the Purwaharja Sector Police of the City of Banjar as many as 30 people, so the authors took samples using a saturated sampling technique so that the number of samples in this study were 30 people. Analysis was carried out on the data collected both from the results of observations, interviews, and questionnaires. The stages of data analysis begin with validity, reliability and verification/quantitative data analysis. The results of the study show that: 1) The need for self-actualization in the Purwaharja Sector Police in Banjar City has been good so far, because it is in accordance with the indicators of the need for actualization which show it is good. Furthermore, based on the results of testing the hypothesis, it is known that there is a positive and significant influence of self-actualization needs on employee performance in the Purwaharja Sector Police in Banjar City; 2) The award for the Purwaharja Sector Police in Banjar City has been good so far, because it has been in accordance with the award indicators which show it has been good. Furthermore, based on the results of testing the hypothesis, it is known that there is a positive and significant influence on employee performance in the Banjar City Purwaharja Sector Police; 3) The performance of employees in the Purwaharja Sector Police of the City of Banjar so far is high, because it is in accordance with work performance indicators which show it is already good. Furthermore, based on the results of testing the hypothesis, it is known that there is a positive and significant influence on the need for self-actualization and respect for employee performance in the Purwaharja Sector Police in Banjar City. This means that the better self-actualization and appreciation, the work performance of the Police will increase.